Modeling Politics with Economic Tools : A Critical Survey of the Literature - Olters, Jan-Peter. (Washington, D.C. : International Monetary Fund, 2001)
Whereas the economics discipline possesses a highly refined theoretical apparatus to analyze the effects of government behaviour on the economy, it has not (yet) managed to fully develop a positively formulated "economic theory of politics" that would permit the integration of the decision-making processes of voters, parties and governments with those of consumers and firms. Considerable recent advances notwithstanding, the large and heterogeneous body of literature has (so far) remained outside the economic mainstrain. The paper surveys the main approaches used to endogenize democratic elements and assesses the underlying reasons for researchers' renewed interest in this field.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet